Epidemiological Characteristics of Meningococcal Meningitis (2016 to 2018) Four Years after the Introduction of Serogroup A Meningococcal Conjugate Vaccine in Benin - Togbemabou Primous Martial Godjedo; Alidehou Jerrold Agbankpe; Moussiliou Noël Paraiso; Tamegnon Victorien Dougnon; Marie Hidjo; Lamine Baba-Moussa; Honore Bankole (Hindawi Limited, 2020)
Objectives. This study aims to study the epidemiological and geographic characteristics of the meningococcal serogroups four years after the introduction of serogroup A meningococcal conjugate vaccine. Methods. This is a prospective, descriptive, analytical study, and it took place from 2016 to 2018. Cerebrospinal fluid (CSF) samples were taken after the identification of meningitis cases. The samples, thus, taken were sent to the laboratory for culture and identification of Neisseria meningitidis in accordance with WHO standards. Results. Eight hundred and ninety-nine bacterial strains were identified, of which 219 were strains of Neisseria meningitidis. The majority of N. meningitidis-positive samples were from male patients (59.8%) with a median age of 4 (IQR: 1-13). Four of N. meningitidis serogroups were identified, namely, serogroups C (6.8%), W (19.6%), X (1.8%), and A (0.5%). Geographically, 92.7% of the identified N. meningitidis serogroups came from patients who lived in the northern region of the country. The departments most concerned were Alibori (N. meningitidis C (66.7%) and N. meningitidis W (20.9%)); Atacora (N. meningitidis W (41.9%), N. meningitidis X (75.0%), and N. meningitidis C (13.3%)); and Borgou (N. meningitidis W (23.3%)). Conclusion. The results of this study showed that there is an emergence of cases of meningococcal of serogroup C four years after the introduction of MenAfricVac in Benin. These results demonstrated the effectiveness of case-by-case surveillance in detecting small changes in the distribution of serogroups that could have important implications for public health strategies in the coming seasons.